The effect of trichloroacetic acid on water-soluble fractions from Fynbo cheese - Sihufe, Guillermo Adrian (2005)
The effect of 4% trichloroacetic acid (TCA) on peptide separation of the water-soluble fraction was analysed during Fynbo cheese ripening. The water-soluble fraction and 4% TCA-soluble sub-fraction were analysed by RP-HPLC. The information of the chromatograms was successfully summarized in 2 dimensions, accounting for 84.7% of data variation using principal component analysis. Peaks that eluted after 30 min in the chromatographic run were most affected by the TCA treatment. Some differences in the amino acid composition were observed between peaks with different signs of the PC2 loading. The TCA extraction and RP-HPLC profiles of the soluble compounds may help in the peptide analysis during Fynbo cheese ripening.